Data-Based Educational Planning Through Utilization Of Educational Reports At The Education Office Of North Central Timor District, East Nusa Tenggara - Johanes Oenaimnou; Masduki Ahmad; Desi Rahmawati (International Conference On Digital Advanced Tourism Management And Technology, 2023)
Based on Government Regulation Number 57 of 2001 concerning National Education Standards & Minister of Education, Culture, Research and Technology Regulation Number 09 of 2022 concerning Evaluation of the Education System by Regional Governments for Early Childhood, Primary and Secondary Education, an Educational Report Platform has emerged to help staff education and those responsible for education in improving the quality of education. Starting from the issue of the quality of Indonesian education, according to the Central Statistics Agency, Sakernas data (2018) recorded that the population of North Central Timor aged 15 years and over who worked was mostly elementary school graduates or below at 65.78%. Meanwhile, Diploma graduates or above only amounted to 11.10%. Apart from that, the School Participation Rate in 2018 for the population aged 7-12 years (SD) was 99.48% who attended school while the rest did not, the population aged 13-15 years (SMP) attended school 92.75% while the rest did not, the population aged 16-18 years old (SMA) who attend school are 64.97% while the rest are not. So, data-based educational planning is needed through education reports. This research was conducted at the North Central Timor Regency Education Service, East Nusa Tenggara using a qualitative approach, and the research objects were the Head of the Education Service and service operators. The results of the research illustrate data-based educational planning that contains holistic student learning outcomes from both cognitive and non-cognitive (character) aspects and encourages educational units and education offices to make improvements through preparing achievement improvement activities based on the results of identification and reflection on achievements. Educational report cards that are appropriate to the field conditions of educational units by carrying out three stages of the Data Based Planning (PBD) process, namely Identification, Reflection, and Improvement (IRB).